Decoding the epics of sustainable world: Sustainalism - Hariram, Nediyirippil Prakasan; Mekha, K. B.; Suganthan, Vipinraj; Sudhakar, Kumarasamy (Elsevier, 2024)
As humanity grapples with the pressing issues of unsustainable practices, the concept of Sustainalism emerges as a transformative approach aimed at achieving global happiness and fostering world peace. The paper critically examines the existing sustainability frameworks and proposes sustainalism as a comprehensive socio-economic- environmental theory with a strong philosophical foundation. Drawing upon diverse disciplines including economics, philosophy, technology, and environmental science, sustainalism advocates for a holistic approach to address these challenges, offering practical pathways towards a more harmonious world. By synthesizing elements from minimalism, naturalism, environmentalism, and gandhism, sustainalism presents a compelling vision for sustainable living and societal harmony. It serves as a catalyst for positive societal change, fostering an egalitarian society grounded in principles of equity and justice. However, several barriers hinder the widespread adoption of Sustainalism, with stakeholders and advanced AI technologies playing pivotal roles in shaping its trajectory. By addressing these barriers and fostering collective action, sustainalism holds the promise of steering humanity toward a brighter, more sustainable future for generations to come.